2002
DOI: 10.1086/342510
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruziParasitemia in Chronic Chagas Disease: Comparison between Human Immunodeficiency Virus (HIV)–Positive and HIV‐Negative Patients

Abstract: This study evaluated Trypanosoma cruzi parasitemia in persons with chronic Chagas disease, compared the parasitemia in human immunodeficiency virus (HIV)-positive and -negative subjects, and, for HIV-positive subjects, analyzed the association between parasitemia and occurrence of acquired immunodeficiency syndrome-defining illnesses, CD4 cell counts, HIV loads, and antiretroviral therapy. In total, 110 adults with chronic Chagas disease (29 HIV positive, 81 HIV negative) were studied. T. cruzi parasitemia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 14 publications
(31 reference statements)
1
53
0
5
Order By: Relevance
“…However, the Th1/Th2 balance seems to positively affect the parasitemia, since patients with positive parasitemia exhibit a predominance of Th2-like response. In this sense, it was observed that T. cruzi parasitemia was significantly more frequent among HIV infected patients 20 . These results confirm …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the Th1/Th2 balance seems to positively affect the parasitemia, since patients with positive parasitemia exhibit a predominance of Th2-like response. In this sense, it was observed that T. cruzi parasitemia was significantly more frequent among HIV infected patients 20 . These results confirm …”
Section: Resultsmentioning
confidence: 95%
“…The impairment of immunity observed in patients infected by HIV provides an opportunity for investigation of the host-defense mechanism. In the course of T. cruzi HIV coinfection, various manifestations can be observed, ranging from severe reactivation of Chagas' disease, with central nerve system involvement, to no clinical manifestation of Chagas' disease with undetectable parasitemia 20 . In experimental T. cruzi infections, during the acute phase, the participation of Th1 immune responses seems to be fundamental for the control of the parasitemia 1 21 , while antibodies seem to be involved in the control of the parasitemia in the chronic phase of the infection 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The histopathological evaluation was reported in only 15% of the cases, with the places most studied the central nervous system (70%) and the myocardium (14%), places where the Chagas disease usually has its most severe forms during the acute phase 96 . Also, were described histopathological evaluations in the stomach 32 , duodenum 51 , skin 48,61,81 and uterine cervix 55 . In all this locations were found parasites and inflammatory reaction suggestive of the Chagas disease.…”
Section: Casesmentioning
confidence: 99%
“…However, just as there are difficulties to know the exact number of individuals co-infected, this also occurs regarding the frequency that these reactivate the Chagas disease, a pathognomonic clinical event. However, when the parasitemia is analyzed by xenodiagnosis or blood culture, the co-infected individuals have a higher chagasic parasitemia than patients without the co-infection with the HIV, suggesting that this reactivation may occur asymptomatic, with a higher frequency 44,60,61 . In this revision, it was reported the occurrence of 41,2% of reactivations, this percentage higher than the ones related in series of cases, which varies between 10 and 15% 81,93,97 , reflecting that, probably, the more severe cases must have been diagnosed and related.…”
Section: Casesmentioning
confidence: 99%
“…In a study conducted by Sartori, Trypanosoma cruzi parasitemia was detected significantly more frequently in HIV-positive than in HIV-negative subjects, and HIV-infected patients also had higher levels of parasitemia 5 .…”
Section: Discussionmentioning
confidence: 95%